1991
DOI: 10.1111/j.1399-302x.1991.tb00499.x
|View full text |Cite
|
Sign up to set email alerts
|

Predominant cultivable flora in pericoronitis

Abstract: The predominant cultivable flora in pericoronitis was investigated by culturing pus from affected sites in 20 patients. Twenty colonies were picked at random from non-selective plates and identified using conventional biochemical and physiological tests, analysis of metabolic end-products by gas chromatography and protein profile analysis. The most frequently isolated organisms were Prevotella (Bacteroides) intermedia, Peptostreptococcus micros, Veillonella species, Fusobacterium nucleatum and Streptococcus mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 19 publications
(19 reference statements)
1
24
0
Order By: Relevance
“…The genus Eubacterium includes more than 40 species exhibiting diverse morphologies and shows biochemical, physiological, and serological heterogeneity (4,11,21,22,25,28,33). We have found that the oral Eubacterium species are clearly distinguished by serological reactions (24), and this immunological heterogeneity suggests that they are a genetically heterogeneous group of microorganisms.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…The genus Eubacterium includes more than 40 species exhibiting diverse morphologies and shows biochemical, physiological, and serological heterogeneity (4,11,21,22,25,28,33). We have found that the oral Eubacterium species are clearly distinguished by serological reactions (24), and this immunological heterogeneity suggests that they are a genetically heterogeneous group of microorganisms.…”
mentioning
confidence: 94%
“…Recognized among them in the past decade are many new species of Eubacterium (e.g., Eubacterium brachy, E. nodatum, E. timidum, E. yurii, and E. saphenum). Some of these species are associated with moderate and severe periodontitis and are less frequent in the supragingival sites or subgingival sites of healthy persons (13,19,32,34,35).The genus Eubacterium includes more than 40 species exhibiting diverse morphologies and shows biochemical, physiological, and serological heterogeneity (4,11,21,22,25,28,33). We have found that the oral Eubacterium species are clearly distinguished by serological reactions (24), and this immunological heterogeneity suggests that they are a genetically heterogeneous group of microorganisms.…”
mentioning
confidence: 99%
“…The microbial flora that develops in the distally located pseudopocket is the major cause. This flora is predominantly anaerobic (3,14,17,19,20,23,26). Therapeutic management usually involves a local surgical procedure and the prescription of antibiotics, often of the ␤-lactam family (7).…”
mentioning
confidence: 99%
“…15 .also reported that less common oral species, such as staphylococci, enteric species, and yeasts, were recovered from failing implants. The peri-implant microbiota differs depending on whether the individual is edentulous or partially edentulous.In particular, P. gingivalis was rarely isolated from edentulous individuals 16, which makes an interesting analogy to the paucity of P. gingivalis isolated from patients with pericoronitis 17 and those in the early stages of periodontitis 18. suggesting that in both cases the deeper periodontal pocket niches favored by P. gingivalis were missing. The microbiota of healthy and diseased dental implants appears to differ depending on the suspected etiology of implant symptoms.…”
Section: Microbiota Associated With Pimentioning
confidence: 99%